Resting echocardiographic predictors for true‐severe aortic stenosis in patients with low‐gradient severe aortic stenosis: A dobutamine stress echocardiography study. Issue 10 (23rd September 2021) - Onishi, Hirokazu; Izumo, Masaki; Mitomo, Satoru; Naganuma, Toru; Nishikawa, Haruka; Suzuki, Tomomi; Sato, Yukio; Watanabe, Mika; Kuwata, Shingo; Kamijima, Ryo; Akashi, Yoshihiro J.; Nakamura, Sunao
Abstract: Objective: Dobutamine stress echocardiography (DSE) is not always feasible in patients with low‐gradient severe aortic stenosis (LG‐SAS), and there are limited data available on the resting echocardiographic predictors for true‐severe aortic stenosis (TSAS). This study investigated resting echocardiographic predictors for TSAS. Methods: Clinical data of 106 LG‐SAS patients who underwent DSE were retrospectively analyzed. LG‐SAS was defined as an aortic valve area index (AVAi) < .6 cm 2 /m 2, and a mean AV pressure gradient < 40 mm Hg. The velocity ratio (VR) was calculated as the peak left ventricular outflow tract velocity/peak AV velocity. TSAS was defined as a projected AVAi < .6 cm 2 /m 2 . Results: The mean age was 79.3 ± 7.3 years, and 45 (42.5%) were men. The resting AV data were as follows: AVAi, .50 ± .07 cm 2 /m 2 ; mean AV pressure gradient, 23.0 ± 7.4 mm Hg; and VR, .25 ± .05. The projected AVAi was .58 ± .09 cm 2 /m 2, and TSAS was documented in 65 (61.3%) patients. In multivariate analysis, the independent predictors of TSAS were AVAi ( p  = 0.012) and VR ( p  = 0.004) with respective best cut‐off values of .52 cm 2 /m 2 and .25 on receiver‐operating characteristic curve analysis. According to incremental numbers of the predictors, correct classification percentages of TSAS significantly increased with the Cochran‐Armitage trend test (16.2% in no predictors, 65.2% in one predictor, and 95.7 % in two predictors; p  < 0.001). Conclusions: Resting AVAi and VR were independent predictors of TSAS in LG‐SAS patients. The true severity might be predictable using the combination of resting parameters.